Paternalism to partnership : the administration of Indian affairs, 1786-2021 - DeJong, David H. (Book collections on Project MUSE., 2022)
"Paternalism to Partnership examines the administration of Indian affairs from 1786, when the first federal administrator was appointed, through 2021. David H. DeJong examines each administrator through a biographical sketch and excerpts of policy statements defining the administrator's political philosophy, drawn from official reports or the administrator's own writings. The Indian Office, as an executive agency under the Secretary of War (1789 to 1849) and secretary of the interior (1849 to present), was directed by the president of the United States. The superintendents, chief clerks, commissioners, and assistant secretaries for Indian affairs administered policy as prescribed by Congress and the president. Each was also given a level of discretion in administering this policy. For most of the federal-Indian relationship, administrators were limited in influencing policy. This paternalism continued well into the twentieth century. Beginning in the 1960s Congress and the president ameliorated their views on the federal-Indian relationship and moved away from paternalism. Since 1966 every administrator of the Bureau of Indian Affairs has been Native American, and each has exercised increasing authority in shaping policy. This has given rise to a federal-Indian partnership that has witnessed tribal nations again exercising their inherent rights of self-government. In this documentary history David H. DeJong follows the progression of federal Indian policy over more than two hundred years, providing firsthand accounts of how the federal-Indian relationship has changed over the centuries"--